2021
DOI: 10.1002/jbt.22939
|View full text |Cite
|
Sign up to set email alerts
|

Genistein suppresses ox‐LDL‐elicited oxidative stress and senescence in HUVECs through the SIRT1‐p66shc‐Foxo3a pathways

Abstract: The anti-senescence function of genistein is related to inhibiting oxidative stress, however, the mechanism has not been clarified. The present study aimed to explore the effects of genistein on oxidized low-density lipoprotein (ox-LDL)-induced endothelial senescence and the role of the sirtuin-1 (SIRT1)-66-kDa Src homology 2 domain-containing protein (p66Shc)-forkhead box protein O3 (Foxo3a) pathways in the process. In this paper, human umbilical vein endothelial cells were pretreated with 1000 nM genistein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Concerning senescence, genistein alleviates the genotoxicity and the cytotoxicity triggered by UVB exposure in human dermal fibroblasts [ 277 ]. Mechanistically, genistein reduces OS-induced senescence by mitigating the levels of mitochondrial ROS and of the DNA oxidation marker 8-OHdG, as well as by upregulating the SIRT1-FOXO3 axis, which is known to prevent aging [ 278 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning senescence, genistein alleviates the genotoxicity and the cytotoxicity triggered by UVB exposure in human dermal fibroblasts [ 277 ]. Mechanistically, genistein reduces OS-induced senescence by mitigating the levels of mitochondrial ROS and of the DNA oxidation marker 8-OHdG, as well as by upregulating the SIRT1-FOXO3 axis, which is known to prevent aging [ 278 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Sirt1 is related to regulating the expression of p66Shc, and the level of p66Shc is reduced in rats with knockout of Sirt1 gene, while the level of p66Shc can be restored by transfection of Sirt1 gene [75]. Sirt1 is a nicotinamide adenine dinucleotide (NAD +) dependent enzyme which can catalyze the deacetylation of lysine residues of histone and participate in the regulation of multiple vital movement such as proliferation, growth and activation [76,77].…”
Section: Sirt1/p66shc Signaling Pathwaymentioning
confidence: 99%
“… 7 Ling et al. 8 , 25 , 26 , 27 reported that the DNA methylation of p66shc is regulated by SAHH, with SAHH inhibition inducing endothelial dysfunction; p66shc exerts its effect through both replicative aging and stress-induced premature aging of hepatocytes, endothelial cells, and renal tubular cells. In our experiments, the expression of SAHH was decreased in both in vitro and in vivo DCM models.…”
Section: Discussionmentioning
confidence: 99%